Territorial and occupancy behavior of black sea bass on oyster aquaculture gear and boulder habitat - Adam D. Armbruster; Renee Mercaldo-Allen; Julie M. Rose; Kristen Seda; Paul Clark; Gillian Phillips; Dylan Redman; Christian W. Conroy (Frontiers in Marine Science, 2024)
Observations of fish behavior can provide insights into habitat preferences and use. Black sea bass, Centropristis striata , are a territorial temperate reef finfish species known for their high commercial and recreational value and association with structured habitat. We used underwater action cameras to record video of black sea bass to assess territorial (agonistic, ambush, displacement) and occupancy (station-keeping) behaviors on shelf and bag style oyster aquaculture cages at a shellfish farm, and on boulders at a natural rock reef near Milford, Connecticut in Long Island Sound, Northwest Atlantic. Black sea bass at a variety of life stages were highly associated with cages, including young-of-the-year, and age 1+ fish. The high abundance of black sea bass observed on cages relative to boulders suggests this species has an affinity for the vertical structure created by aquaculture gear. When behaviors were normalized to the total fish sightings, black sea bass showed no significant difference in frequency of behaviors between habitats, indicating that per-fish rates of behavior were similar on cages and boulders. Demonstration of territorial and occupancy behaviors by black sea bass on, and around cages suggests that aquaculture gear provides structured habitat and ecosystem services for this species similar to natural reefs.These results suggest that essential fish habitat descriptions of manmade structures used by black sea bass could be broadened to include aquaculture gear. Our study provides novel information on behavioral interactions of black sea bass with oyster cages that may support aquaculture permitting and consultation processes.

Global gradients in intraspecific variation in vegetative and floral traits are partially associated with climate and species richness - Jonas Kuppler; Cécile H. Albert; Gregory M. Ames; William Scott Armbruster; Gerhard Boenisch; Florian C. Boucher; Diane R. Campbell; Liedson T. Carneiro; Eduardo Chacón‐Madrigal; Brian J. Enquist; Carlos R. Fonseca; José M. Gómez; et al. (Global Ecology and Biogeography, 2020)
Aim Intraspecific trait variation (ITV) within natural plant communities can be large, influencing local ecological processes and dynamics. Here, we shed light on how ITV in vegetative and floral traits responds to large‐scale abiotic and biotic gradients (i.e., climate and species richness). Specifically, we tested whether associations of ITV with temperature, precipitation and species richness were consistent with any of four hypotheses relating to stress tolerance and competition. Furthermore, we estimated the degree of correlation between ITV in vegetative and floral traits and how they vary along the gradients. Location Global. Time period 1975–2016. Major taxa studied Herbaceous and woody plants. Methods We compiled a dataset of 18,401 measurements of the absolute extent of ITV (measured as the coefficient of variation) in nine vegetative and seven floral traits from 2,822 herbaceous and woody species at 2,372 locations. Results Large‐scale associations between ITV and climate were trait specific and more prominent for vegetative traits, especially leaf morphology, than for floral traits. The ITV showed pronounced associations with climate, with lower ITV values in colder areas and higher values in drier areas. The associations of ITV with species richness were inconsistent across traits. Species‐specific associations across gradients were often idiosyncratic, and covariation in ITV was weaker between vegetative and floral traits than within the two trait groups. Main conclusions Our results show that, depending on the traits considered, ITV either increased or decreased with climate stress and species richness, suggesting that both factors can constrain or enhance ITV, which might foster plant‐population persistence in stressful conditions. Given the species‐specific responses and covariation in ITV, associations can be hard to predict for traits and species not yet studied. We conclude that consideration of ITV can improve our understanding of how plants cope with stressful conditions and environmental change across spatial and biological scales.

Species delimitation based on integrative approach suggests reallocation of genus in Hypostomini catfish (Siluriformes, Loricariidae) - Marcia S. Anjos; Jamille A. Bitencourt; Lorena A. Nunes; Luisa M. Sarmento-Soares; Daniel C. Carvalho; Jonathan W. Armbruster; Paulo R. A. M. Affonso (Hydrobiologia, 2020)

Can members of the south‐western Gila robusta species complex be distinguished by morphological features? - C. J. Moran; M. W. O'Neill; J. W. Armbruster; A. C. Gibb (Journal of Fish Biology, 2017)
The goal for this project was to re‐examine key morphological characters hypothesized to differentiate Gila intermedia , Gila robusta and Gila nigra and outline methods better suited for making species designations based on morphology. Using a combination of meristic counts, morphological measurements and geometric morphometrics, morphological dissimilarities were quantified among these three putative species. Traditional meristic counts and morphological measurements ( i.e. distances between landmarks) were not useful for species identification. Geometric morphometrics, however, identified differences among species, while also suggesting an effect of geographic location on morphological variation. Using canonical variate analysis for the 441 fish sampled in this study, geometric morphometrics accurately predicted true group membership 100% of the time for G . nigra , 97% of the time for G . intermedia and 91% of the time for G . robusta . These results suggest that geometric morphometric analysis is necessary to identify morphological differences among the three species. Geometric morphometric analysis used in this study can be adopted by management officials as a tool to classify unidentified individuals.

An empirical test for convergence using African barbs (Cypriniformes: Cyprinidae) - Jonathan W. Armbruster; Carla C. Stout; Malorie M. Hayes (Evolutionary Ecology, 2016)

Disjunct populations of E uropean vascular plant species keep the same climatic niches - Safaa Wasof; Jonathan Lenoir; Per Arild Aarrestad; Inger Greve Alsos; W. Scott Armbruster; Gunnar Austrheim; Vegar Bakkestuen; H. John B. Birks; Kari Anne Bråthen; Olivier Broennimann; Jörg Brunet; Hans Henrik Bruun; et al. (Global Ecology and Biogeography, 2015)
Aim Previous research on how climatic niches vary across species ranges has focused on a limited number of species, mostly invasive, and has not, to date, been very conclusive. Here we assess the degree of niche conservatism between distant populations of native alpine plant species that have been separated for thousands of years. Location European A lps and F ennoscandia. Methods Of the studied pool of 888 terrestrial vascular plant species occurring in both the A lps and F ennoscandia, we used two complementary approaches to test and quantify climatic‐niche shifts for 31 species having strictly disjunct populations and 358 species having either a contiguous or a patchy distribution with distant populations. First, we used species distribution modelling to test for a region effect on each species' climatic niche. Second, we quantified niche overlap and shifts in niche width (i.e. ecological amplitude) and position (i.e. ecological optimum) within a bi‐dimensional climatic space. Results Only one species (3%) of the 31 species with strictly disjunct populations and 58 species (16%) of the 358 species with distant populations showed a region effect on their climatic niche. Niche overlap was higher for species with strictly disjunct populations than for species with distant populations and highest for arctic–alpine species. Climatic niches were, on average, wider and located towards warmer and wetter conditions in the Alps. Main conclusion Climatic niches seem to be generally conserved between populations that are separated between the A lps and F ennoscandia and have probably been so for 10,000–15,000 years. Therefore, the basic assumption of species distribution models that a species' climatic niche is constant in space and time – at least on time scales 10 4 years or less – seems to be largely valid for arctic–alpine plants.

Plumbing of hospital premises is a reservoir for opportunistically pathogenic microorganisms: a review - Margaret M. Williams; Catherine R. Armbruster; Matthew J. Arduino (Biofouling, 2013)

A biofilm model developed to investigate survival and disinfection of Mycobacterium mucogenicum in potable water - Catherine R. Armbruster; Terri S. Forster; Rodney M. Donlan; Heather A. O'Connell; Alicia M. Shams; Margaret M. Williams (Biofouling, 2012)

Nitrogen input together with ecosystem nitrogen enrichment predict nitrate leaching from European forests - J. A. MacDonald; N. B. Dise; E. Matzner; M. Armbruster; P. Gundersen; M. Forsius (Global Change Biology, 2002)
The IFEF database (Indicators of Forest Ecosystem Functioning), consisting of nitrogen deposition, nitrate leaching fluxes, and soil and ecosystem characteristics, is analysed to evaluate the C/N ratio in the organic horizon as an indicator of nitrate leaching. One hundred and eighty one forests are examined, from countries across Europe ranging from boreal to Mediterranean regions, encompassing broadleaf and coniferous sites and plot and catchment studies. N input in throughfall ranges from less than 1 kg N ha −1 y −1 in northern Norway and Finland to greater than 60 kg N ha −1 y −1 in the Netherlands and Czech Republic. The amount of NO 3 – leached covers a smaller range, between 1 and 40 kg N ha −1 y −1 . Nitrate leaching is strongly dependent on the amount of nitrogen deposited in throughfall (N input) and simply adding the C/N ratio in the organic horizon to a regression equation does not improve this relationship. However, when the data are stratified based on C/N ratios less than or equal to 25 and greater than 25, highly significant relationships ( P 3 – leached. The slope of the relationship for those sites where C/N ratio is ≤ 25 (′nitrogen enriched′ sites) is twice that for those sites where C/N ratio is > 25. These empirical relationships may be used to identify which forested ecosystems are likely to show elevated rates of nitrate leaching under predicted future nitrogen deposition scenarios. Elevated NO 3 – leaching also shows a relationship with soil pH, with high rates of NO 3 – leaching only observed at sites with a pH 30 kg N ha −1 y −1 . Tree age and species have no significant impact on the ecosystem response to N input at a regional scale.